1955
DOI: 10.1079/pns19550026
|View full text |Cite
|
Sign up to set email alerts
|

Some Traditional Alcoholic Beverages and their Importance in Indigenous African Communities

Abstract: Fermented honey drinks may have been the earliest alcoholic beverages known to man and the discovery of them has been attributed to the Hamites (Seyffert, 1930).Another hypothesis of the origin of alcoholic liquors is that they were first encountered when wild fruits were stored in clay-lined holes in the ground (Renard, 1929). If beer was not in fact originally brewed by man in Africa, some alcoholic fermentations were developed on that continent. According to the mythology of the Egyptians, their first queen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1957
1957
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…The bride price usually paid in cows was traditionally accompanied by several pots of beer' [6]. Platt found an almost identical situation among several ethnic groups in the Rift Valley in Kenya [3]. In addition, he found that collective work, one of the most remarkable features of rural African life (e.g.…”
Section: Traditional Use and Role Of Alcohol In East African Societymentioning
confidence: 99%
See 4 more Smart Citations
“…The bride price usually paid in cows was traditionally accompanied by several pots of beer' [6]. Platt found an almost identical situation among several ethnic groups in the Rift Valley in Kenya [3]. In addition, he found that collective work, one of the most remarkable features of rural African life (e.g.…”
Section: Traditional Use and Role Of Alcohol In East African Societymentioning
confidence: 99%
“…It has been claimed that the mountainous area of Ethiopia in East Africa was one of the seven (fundamental) centres of the world where cultivated plants used for alcohol production originated [3]. These plants, namely wheat, barley, sorghum, maize, millet, cassava, bananas, to mention few, have been cultivated here traditionally for food and cash.…”
Section: Historical Perspectivementioning
confidence: 99%
See 3 more Smart Citations